STUDI MORFOMETRIK DAN MERISTIK UDANG MANTIS (ORATOSQUILLINA GRAVIERI) DI PERAIRAN PESISIR PERCUT SEI TUAN PROVINSI SUMATERA UTARA - Memory Oktavia Sihombing; Hasan Sitorus; Rusdi Leidonald (AQUACOASTMARINE, 2018)
Mantis Shrimp (Oratosquilla gravieri) is one of the water resources that has highly economic potential but in the waters of the Sei Tuan has not been optimally utilized. The research of morphometrics and meristir were used for identification, growth model analysis, and management efforts for Mantis Shrimp resourse. The research was conducted in December 2017 in the seawaters of the Percut Sei Tuan. Catching of shrimp was conducted on 3 stations with a total sample of 90 shrimps. The length of Mantis Shrimp that caught during the study was 8.10 cm to 16.9 cm. Correlation between morphometric characters is very strong with correlation coefficient (r) ranged from 0.774 to 0.992. In Mantis Shrimp meristic was obtained 4 to 6 pieces of thorns on telson, 6 thorns on dactylus and 0 to 2 thorns on propodus. Mantis Shrimp growth pattern in Percut water was negative allometric with b value ranged from 2.212 to 2.326 (b <3).Keywords : Morphometrics, Meristics, Water Quality, Mantis Shrimp, Percut Sei Tuan